Deaths in children in England from SARS-CoV-2 infection during the first 2 years of the pandemic: a cohort study - Shamez N Ladhani; Peter Fleming; Tom Williams; Karen Luyt; Godwin Oligbu; David Odd; Sylvia Stoianova; Anna Thursby-Pelham (BMJ Open)
Objective The aim of this analysis was to describe the epidemiology, demographics and characteristics of children and young people (CYP) who died of SARS-CoV-2 infection in England during the first 2 years of the pandemic.Design The cohort investigated in this study is all CYP, born alive at, or after, 22 weeks of gestation, who died before their 18th birthday between 1 February 2020 and 31 March 2022 in England. All cases were reviewed to identify if SARS-CoV-2 probably, or possibly, contributed to death. Mortality rates were calculated, assuming a Poisson distribution, for the whole population, and split by demographics and patient characteristics.Setting England.Participants 6389 CYP deaths in England reported to the National Child Mortality Database (NCMD).Main outcome Risk of death.Results 88 of the 6389 deaths of CYP were identified as deaths probably due to COVID-19. Thus, COVID-19 was responsible for 1.4% of all deaths of CYP in this 26-month period. Overall mortality rate due to COVID-19 in CYP was 3.59 (2.88–4.42) per 1 000 000 person years, being highest in the youngest (< 5 years; 4.68 (3.16–6.68)) and oldest (16/17 years; 4.83 (2.57–8.26)) CYP. Asian and Black CYP had higher mortality than those from white backgrounds (p<0.001), and mortality rate increased with increasing deprivation. The majority (61/77, 79.2) of CYP who died of COVID had a documented life limiting condition.Conclusions Mortality rates were highest in less than 5 years old. Despite social changes, and shielding of vulnerable CYP, children with life-limiting (but not necessarily life-threatening) conditions, appeared to have the highest mortality rates, similar to that seen in adults with comparable underlying conditions. The risk of death in more deprived neighbourhoods and in those from Asian and Black ethnic backgrounds was increased, and this was not explained by their other demographic characteristics.